Shiver [compact disc, unabridged] - Stiefvater, Maggie, 1981- (Stiefvater, Maggie, 1981- Wolves of Mercy Falls, 2009)
In all the years she has watched the wolves in the woods behind her house, Grace has been particularly drawn to an unusual yellow-eyed wolf who, in his turn, has been watching her with increasing intensity.